2011
DOI: 10.3109/11038128.2011.627378
|View full text |Cite
|
Sign up to set email alerts
|

The myth of participation in occupational therapy: reconceptualizing a client-centred approach

Abstract: Participation is often the comprehensive objective of treatment but also an indication of the extent to which the process of occupational therapy is client-centred. The purpose of this study was to explore levels of participation during occupational therapy among clients in the area of mental health from the occupational therapists' perspectives.Additionally we seek to identify factors that might hinder client participation. Postal questionnaires were sent out to 670 Swedish occupational therapists working wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
20
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 12 publications
6
20
1
Order By: Relevance
“…The participants allowed the clients to direct the visits to a large extent, and they paid conscious attention to the clients' wishes and goals. This is in line with the view that a client-centered approach builds on an interdependent collaboration between the professionals and the client rather than on an independent goal setting (Kjellberg, Kåhlin, Haglund, & Taylor, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…The participants allowed the clients to direct the visits to a large extent, and they paid conscious attention to the clients' wishes and goals. This is in line with the view that a client-centered approach builds on an interdependent collaboration between the professionals and the client rather than on an independent goal setting (Kjellberg, Kåhlin, Haglund, & Taylor, 2012).…”
Section: Discussionsupporting
confidence: 61%
“…The individual´s perspective, needs, and desires should thus be the driving force of support and service. This is also in line with the concept of occupational justice (37) and the person-centred approach within occupational therapy, which recognize an individual's knowledge, strengths, capacity for choice, and overall predisposition toward empowerment (63)(64). Based on this, occupational therapy interventions can and should support choice and control in people ageing with ID.…”
Section: Discussionmentioning
confidence: 63%
“…the client". And indeed, these are exactly the barriers to client participation identified by occupational therapists in a recent study (34). Insidious power is expressed in the carefully constructed discourses that protect and promote vested professional interests, thus little attention has been focused on clients' perceptions of those professional practices that constitute barriers to client-centred occupational therapy.…”
Section: Challenging Professional Powermentioning
confidence: 97%
“…A considerable quantity of research has explored perceived barriers to client-centred clinical practice from the perspective of occupational therapists (20,34), much of which is premised on the assumption "that clients present many barriers that will inhibit their involvement in client-centred practice" [(93), p. 14]. From his observations of occupational therapy, Abberley [(38), p. 242] accordingly observed that "failure, [of intervention], in so far as it is acknowledged, tends to be attributed to forces beyond the therapist's control.…”
Section: Challenging Professional Powermentioning
confidence: 99%
See 1 more Smart Citation